Wired for story : the writer's guide to using brain science to hook readers from the very first sentence - Cron, Lisa (Ten Speed Press, 2012)
"This guide reveals how writers can take advantage of the brain's hard-wired responses to story to captivate their readers' minds through each plot element"--Provided by publisher.